THE PSYCHOLOGICAL IMPACT OF DIGITAL FRAUD: A PHENOMENOLOGICAL STUDY OF VICTIMS IMPERSONATING PT BANK RAKYAT INDONESIA - Sukmana, Salsabila Tita; Azwar (International Journal of Cultural and Social Science, 2025)
Digital fraud impersonating PT Bank Rakyat Indonesia (BRI) has become an alarming phenomenon that causes financial and psychological harm to victims. This study explores victims’ lived experiences using a phenomenological approach within a qualitative framework through in-depth interviews and social media observations. The findings show that victims experienced not only financial loss but also emotional distress such as panic, trauma, and a decline in trust toward banking institutions. These experiences influenced how victims interpret digital communication, fostering skepticism toward online information. The phenomenological analysis reveals that meaning is constructed through the interaction of language, past experiences, and awareness of new realities after the fraud. The study emphasizes the need for digital literacy, empathetic communication, and preventive education from financial institutions to restore public trust and strengthen resilience against cybercrime.